Arterial remodelling of native human coronary arteries in patients with unstable angina pectoris: a prospective intravascular ultrasound study. Issue 1 (1st July 1999) - Gyöngyösi, M; Yang, P; Hassan, A; Weidinger, F; Domanovits, H; Laggner, A; Glogar, D
Abstract : OBJECTIVE: To investigate the use of intravascular ultrasound (IVUS) in detecting the presence of arterial remodelling in patients with unstable angina. DESIGN: Prospective case study. PATIENTS: 60 of 95 consecutively admitted patients with unstable angina (41 male, 19 female), mean (SD) age 61.2 (8.1) years. INTERVENTIONS: Qualitative and quantitative coronary angiography and IVUS. MAIN OUTCOME MEASURES: Adaptive or constrictive remodelling (AR, CR) was considered present when the cross sectional area of the external elastic membrane at the lesion site was larger than the proximal cross sectional area or smaller than the distal cross sectional area, respectively. RESULTS: 22 of the 60 patients (37%) showed AR and 14 (23%) showed CR. No remodelling was seen in 24 patients (group NR). The plaque contained more thrombus and plaque rupture in group AR than in groups CR and NR (thrombus: 91% v 50% and 67%, respectively, p = 0.023; rupture: 73% v 29% and 42%, p = 0.020). AR was associated with a larger plaque cross sectional area (12.6 (SD 4.6) mm 2 v 10.8 (6.3) and 9.2 (3.7) mm 2, p = 0.001) and larger external elastic membrane cross sectional area (16.5 (5.8) mm 2 v 13.2 (5.2) and 14.4 (3.6) mm 2, p = 0.01 in group AR v groups CR and NR, respectively), while the plaque burden was larger in groups AR (74.9 (9.1)%) and CR (72.4 (16.6)%) than in group NR (66.2 (18.1)%, p = 0.005). CONCLUSIONS: IVUS is capable of detecting adaptive and constrictive remodelling of target lesions and its relation to plaque morphology in unstable angina.